Dynamic Analysis on Hammer of a Coal-Hammer Mill Crusher (International Journal of Current Engineering and Technology, 2014)
The Paper deals with the Static and Dynamic (Modal, Harmonic) analyses for analyzing the hammer used for crushing coal. The size of the coal received is 200 mm and has to be crushed as per the desired sizes (30mm) . The hammers are made of Manganese Steel (SA – 105). Deformation under static analysis is found. Maximum strain value is obtained. The maximum induced stresses and the frequency at which the hammer is to be operated is analyzed. The Hammer is modeled in CATIA and is analyzed by ANSYS software.
Keywords: Hammer mill crusher, Tramp iron, Vibratory Motion, Modal, Harmonic and Dynamic analysis.